2001
DOI: 10.1002/1521-3765(20011105)7:21<4572::aid-chem4572>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Diene-Containing Half-Sandwich MoIII Complexes as Ethylene Polymerization Catalysts: Experimental and Theoretical Studies

Abstract: Seventeen-electron compounds of MoIII having the general formula [(eta5-C5R5)Mo(eta4-diene)X2] (R = H, Me: dieney = butadiene, isoprene, or 2,3-dimethylbutadiene: X= Cl, CH3) are a new class of ethylene polymerization catalysts. The polyethylene obtained shows a bimodal distribution, the major weight fraction being characterized by very long (M around 10(6)) and highly linear polymer chains. The newly prepared pentamethylcyclopentadienyl (Cp*) derivatives are more active than the cyclopentadienyl (Cp) derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…Computational studies have been used to explore the nature of the oxidation state in catalysts derived from Cr VI bis(imido) complexes. , In more recent years, a significant amount of attention has been given to the development of homogeneous non-Cp systems. There have also been two reports of molecular catalysts for ethylene polymerization based on molybdenum, but both the bis(imido)Mo VI Cl 2 precatalyst and the Cp*(butadiene)Mo III Cl 2 system show only very low activities.…”
Section: Group 6 Catalystsmentioning
confidence: 99%
“…Computational studies have been used to explore the nature of the oxidation state in catalysts derived from Cr VI bis(imido) complexes. , In more recent years, a significant amount of attention has been given to the development of homogeneous non-Cp systems. There have also been two reports of molecular catalysts for ethylene polymerization based on molybdenum, but both the bis(imido)Mo VI Cl 2 precatalyst and the Cp*(butadiene)Mo III Cl 2 system show only very low activities.…”
Section: Group 6 Catalystsmentioning
confidence: 99%
“…Examination of this polymer with GPC gave an unusually sharp peak, indicating a living polymerization. R. Poli recently reported that diene half-metallocene molybdenum complexes became catalyst precursors for ethylene polymerization [78]. The mechanism of these catalyst systems was discussed on the basis of DFT calculations [78,79].…”
Section: Functionalized Diene Complexesmentioning
confidence: 99%
“…Therefore, it is necessary to locate and characterize the stationary points on each PES and the key regions of the PESs where the relevant spin states lie close in energy and geometry, corresponding to the crossing points (CPs). Computational methods of theoretical chemistry are suitable tools for the study of this type of phenomenon, and several authors have addressed this complex and demanding research area. , …”
Section: Introductionmentioning
confidence: 99%